2011
DOI: 10.1523/jneurosci.6656-10.2011
|View full text |Cite
|
Sign up to set email alerts
|

Calcium/Calmodulin-Dependent Protein Kinase II Mediates Group I Metabotropic Glutamate Receptor-Dependent Protein Synthesis and Long-Term Depression in Rat Hippocampus

Abstract: Activation of Group I metabotropic glutamate receptors (mGluRs) in rat hippocampus induces a form of long-term depression (LTD) that is dependent on protein synthesis. However, the intracellular mechanisms leading to the initiation of protein synthesis and expression of LTD after mGluR activation are only partially understood. We investigated the role of several pathways linked to mGluR activation, translation initiation, and induction of LTD. We found that Group I mGluR-dependent protein synthesis and associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
125
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(139 citation statements)
references
References 64 publications
13
125
1
Order By: Relevance
“…In contrast to the metaplasticity of LTP in the hippocampus (Bortolotto and Collingridge, 1998), we found CaMKII was not required for this form of metaplasticity in the ACC, though its inhibition did tend to reduce the level of priming. Moreover, a recent study showed in the hippocampus that CaMKII was important in mediating DHPG-induced mGluR-LTD but not PKC (Mockett et al, 2011). These results indicate that intracellular mechanisms mediated by priming group I mGluR in LTD may be doserelated and region-dependent.…”
Section: Loss Of Cortical Ltd After Amputationmentioning
confidence: 76%
“…In contrast to the metaplasticity of LTP in the hippocampus (Bortolotto and Collingridge, 1998), we found CaMKII was not required for this form of metaplasticity in the ACC, though its inhibition did tend to reduce the level of priming. Moreover, a recent study showed in the hippocampus that CaMKII was important in mediating DHPG-induced mGluR-LTD but not PKC (Mockett et al, 2011). These results indicate that intracellular mechanisms mediated by priming group I mGluR in LTD may be doserelated and region-dependent.…”
Section: Loss Of Cortical Ltd After Amputationmentioning
confidence: 76%
“…7e, f). In addition, it was reported that activation of mGluR I may alter CaMKII activity in various types of central neurons (Choe and Wang 2001;Mockett et al 2011). We tested the possible involvement of this signaling pathway.…”
Section: Involvement Of Ca 21 -Dependent Plc/pkc and Camkii Signalingmentioning
confidence: 99%
“…It seems that activation of mGluR I-induced increase in [Ca 2ϩ ] i in rat Müller cells could be due to Ca 2ϩ release from both IP 3 -and ryanodine-sensitive Ca 2ϩ stores. Changes in calcium/calmodulindependent protein kinase II (CaMKII) activity, which have been reported in various types of central neurons (Choe and Wang, 2001;Mockett et al, 2011), were unlikely involved in DHPG-induced suppression of Kir currents in Müller cells. Bath application of CaMKII inhibitors KN-62 (5 M)/KN-93 (10 M) did not change the Kir currents.…”
Section: Camentioning
confidence: 99%